Landasan Teori Perkembangan Sosial Emosional Anak Usia Dini - Asti Sugiarti; Zusy Ariyanti; Dwi Enggal Wahyuni (ALMURTAJA: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Social-emotional development is one of the most important aspects of early childhood education, as it plays a crucial role in shaping children's ability to interact with others, regulate emotions, adapt to their environment, and build positive social relationships. Understanding the theoretical foundations of social-emotional development is essential for designing appropriate educational practices and developmental stimulation that align with children's developmental characteristics. This study aims to analyze and examine the major theoretical foundations of early childhood social-emotional development and to explain their relevance and implementation in supporting children's holistic growth and education. The study employed a qualitative descriptive approach through a literature review method. Data were collected and analyzed from 30 scholarly articles related to early childhood social-emotional development. The findings revealed that Erik Erikson’s Psychosocial Theory, Albert Bandura’s Social Learning Theory, and Lev Vygotsky’s Sociocultural Theory are the primary theoretical foundations explaining social-emotional development in early childhood. Furthermore, the study found that play activities, traditional games, storytelling, as well as support from families and teachers play significant roles in fostering children's social-emotional competencies. The study concludes that early childhood social-emotional development is influenced by the interaction between individual factors and the social environment. Therefore, the implementation of social-emotional development theories should be integrated into educational and parenting practices to promote children's holistic development.